THE EFFECT OF STRESS SYMPTOMS AND COPING STRATEGIES ON FAMILY STRENGTHS IN FAMILIES AFFECTED BY LAYOFFS DURING THE COVID-19 PANDEMIC - Andhini Agustiani Rahmawati; Tin Herawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Layoffs during the Covid-19 pandemic resulted in family stress because there was no income to meet needs so families needed coping strategies in order to maintain their families. The purpose of this study is to analyze the relationship and influence of family characteristics, stress symptoms, and coping strategies on family strengths in families affected by layoffs during the Covid-19 pandemic. The research design used a cross-sectional study. The sampling technique used voluntary sampling with a total of 50 samples. This study uses primary data by distributing online questionnaires using Google Forms. The data obtained were analyzed using the Statistical Package for Social Science (SPSS) for windows version 22. Data analysis in this study was descriptive analysis, Spearman correlation, Pearson correlation, and multiple linear regression. The results showed that there was a significant positive relationship between wife's education and emotional-focused coping. Stress symptoms have a significant positive relationship with problem-focused coping and a significant negative relationship with family strength. Emotional-focused coping has a significant positive relationship with family strength. Regression analysis shows that emotional-focused coping has a significant positive effect on family strength. Symptoms of stress have a significant negative effect on family strength. Families affected by layoffs during the Covid-19 pandemic should be able to minimize symptoms of physical stress by doing breathing relaxation. The related government is also expected to provide family empowerment through increasing entrepreneurial knowledge and skills.